2016
DOI: 10.1016/j.molcel.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The m 6 A Methyltransferase METTL3 Promotes Translation in Human Cancer Cells

Abstract: METTL3 is a RNA methyltransferase implicated in mRNA biogenesis, decay, and translation control through N6-methyladenosine (m6A) modification. Here we find that METTL3 promotes translation of certain mRNAs including epidermal growth factor receptor (EGFR) and the Hippo pathway effector TAZ in human cancer cells. In contrast to current models that invoke m6A reader proteins downstream of nuclear METTL3, we find METTL3 associates with ribosomes and promotes translation in the cytoplasm. METTL3 depletion inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
1,364
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,228 publications
(1,493 citation statements)
references
References 45 publications
(83 reference statements)
67
1,364
5
Order By: Relevance
“…However, surprisingly, METTL3 promoted translation independent of its methyltransferase activity or m 6 A readers, because the catalytic domain of METTL3 showed no effect in promoting translation of the above oncogenes. In addition, knockdown of YTHDF1/YTHDF2 did not influence METTL3‐mediated translation 94. These findings provide us with insight into the mechanisms of m 6 A modification‐related proteins.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 68%
See 1 more Smart Citation
“…However, surprisingly, METTL3 promoted translation independent of its methyltransferase activity or m 6 A readers, because the catalytic domain of METTL3 showed no effect in promoting translation of the above oncogenes. In addition, knockdown of YTHDF1/YTHDF2 did not influence METTL3‐mediated translation 94. These findings provide us with insight into the mechanisms of m 6 A modification‐related proteins.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 68%
“…Other studies find a new paradigm of how METTL3 affects tumour development independent of m 6 A modification 94. Lin et al.…”
Section: The Dual Role Of M6a Modification In Human Cancersmentioning
confidence: 99%
“…Previous evidence showed that oocyte mRNA translation is controlled by two mechanisms: poly(A) tail length-correlated translation efficiency and 3Ј UTR element-mediated mRNA translation activation. Recently, evidence suggested a possible association of translation with RNA methylation (12,16,25), indicating that the 5Ј UTR m 6 A modification could initiate the translation of non-capped mRNAs. Through integrating the m 6 A-seq data and transcriptome/proteome data in X. laevis, we investigated m 6 A modification and possible roles of oocyte mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalent internal RNA modification mark N(6)-methyladenosine (m 6 A) has been reported to play a role in regulating most facets of the RNA life cycle, including regulation of pre-mRNA splicing, mRNA stability, and mRNA translation (Lin et al, 2016;Liu et al, 2015;Wang et al, 2015Wang et al, , 2014Xiao et al, 2016;Zhao et al, 2014). Recently, work by us (Alarcón et al, 2015) and others (Ke et al, 2017;Knuckles et al, 2017) has established that m 6 A marks are deposited in the nucleus and are proposed to function in many nuclear regulatory processes, including microRNA and messenger RNA processing.…”
Section: Introductionmentioning
confidence: 99%